Applying EOQ with Sustainability Metrics in Vaccine Packaging Management - Hadi Susanto; Winarno; Alexandra Elizabeth Callistha; Shakira Dwi Purwandari; Naila Davina Aurelia (Telkom University, 2025)
Sustainable supply chain management (SSCM) is crucial in vaccine distribution, where poor packaging inventory control lead to excessive waste and carbon emissions. This study applies the classical Economic Order Quantity (EOQ) model to optimize vaccine packaging inventory and evaluates its outcomes using sustainability indicators (packaging waste, emergency shipments, and CO2e). A case study at a major Indonesian vaccine manufacturer shows how EOQ-based planning, followed by sustainability impact assessment, improves operational efficiency while reducing environmental burdens. Rather than embedding environmental variables inside the EOQ formula, sustainability is operationalized as a downstream impact-assessment layer that quantifies the consequences of EOQ decisions. Using historical operational data and standard emission factors, results indicate an estimated 50% reduction in packaging surplus and 15% reduction in cold-chain emissions annually when compared with prior practices. These findings position EOQ as a practical decision-support tool that aligns inventory control with SSCM goals in cold-chain logistics.